Quiescent Consistency: Defining and Verifying Relaxed Linearizability - Derrick, John; Dongol, Brijesh; Schellhorn, Gerhard; Tofan, Bogdan; Travkin, Oleg; Wehrheim, Heike (FM 2014: Formal Methods - 19th International Symposium, Singapore, May 12-16, 2014. Proceedings)

Handling TSO in Mechanized Linearizability Proofs - Travkin, Oleg; Wehrheim, Heike (Hardware and Software: Verification and Testing - 10th International Haifa Verification Conference, HVC 2014, Haifa, Israel, November 18-20, 2014. Proceedings)

Timed Automata Verification via IC3 with Zones - Isenberg, Tobias; Wehrheim, Heike (Formal Methods and Software Engineering - 16th International Conference on Formal Engineering Methods, ICFEM 2014, Luxembourg, Luxembourg, November 3-5, 2014. Proceedings)

Managing LTL Properties in Event-B Refinement - A. Schneider, Steve; Treharne, Helen; Wehrheim, Heike; M. Williams, David (Integrated Formal Methods - 11th International Conference, IFM 2014, Bertinoro, Italy, September 9-11, 2014, Proceedings)

Managing LTL properties in Event-B refinement - Schneider, Steve; Treharne, Helen; Wehrheim, Heike; M. Williams, David (CoRR)

Proof-Carrying Hardware via IC3 - Isenberg, Tobias; Wehrheim, Heike (CoRR)

Twenty years of learning with the World Wide Web - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix

Zwischen Design und Flexibilität - Zur Ergonomie des Flat Design - Winkelnkemper, Felix; Keil, Reinhard

ScenarioTools Real-Time Play-Out for Test Sequence Validation in an Automotive Case Study - Brenner, Christian; Greenyer, Joel; Holtmann, Jörg; Liebel, Grischa; Stieglbauer, Gerald; Tichy, Matthias (Proceedings of the 13th International Workshop on Graph Transformation and Visual Modeling Techniques (GT-VMT 2014))
In many areas, such as automotive, healthcare, or production, we find software-intensive systems with complex real-time requirements. To efficiently ensure the quality of these systems, engineers require automated tools for the validation of the requirements throughout the development. This, however, requires that the requirements are specified in an analyzable way. We propose modeling the specification using Modal Sequence Diagrams (MSDs), which express what a system may, must, or must not do in certain situations. MSDs can be executed via the play-out algorithm to investigate the behavior emerging from the interplay of multiple scenarios; we can also test if traces of the final product satisfy all scenarios. In this paper, we present the first tool supporting the play-out of MSDs with real-time constraints. As a case study, we modeled the requirements on gear shifts in an upcoming standard on vehicle testing and use our tool to validate externally generated gear shift sequences.

Nash Equilibria in Shared Effort Games - Polevoy, Gleb; Trajanovski, Stojan; de Weerdt, Mathijs M. (Proceedings of the 2014 International Conference on Autonomous Agents and Multi-agent Systems)
Keywords: competition; equilibrium; market; models; shared effort games; simulation

Improving Human Interaction in Crowdsensing - Polevoy, Gleb; de Weerdt, Mathijs M. (Proceedings of the 2014 International Conference on Autonomous Agents and Multi-agent Systems)
Keywords: dynamics; emotion modeling; negotiation; network interaction; shared effort game

Request Driven Social Sensing - King, Thomas C.; Liu, Qingzhi; Polevoy, Gleb; de Weerdt, Mathijs; Dignum, Virginia; van Riemsdijk, M. Birna; Warnier, Martijn (Proceedings of the 2014 International Conference on Autonomous Agents and Multi-agent Systems)
Keywords: crowd-sensing; crowdsourcing; data aggregation; game theory; norms; reciprocation; self interested agents; simulation

Signaling Competition and Social Welfare - Polevoy, Gleb; Smorodinsky, Rann; Tennenholtz, Moshe (ACM Trans. Econ. Comput.)
Keywords: Competition; efficiency; equilibrium; market; social welfare

Numerical Simulation of the Damping Behavior of Particle-Filled Hollow Spheres - Steinle, Tobias; Vrabec, Jadran; Walther, Andrea (Proc. Modeling, Simulation and Optimization of Complex Processes (HPSC))
In light of an increasing awareness of environmental challenges, extensive research is underway to develop new light-weight materials. A problem arising with these materials is their increased response to vibration. This can be solved using a new composite material that contains embedded hollow spheres that are partially filled with particles. Progress on the adaptation of molecular dynamics towards a particle-based numerical simulation of this material is reported. This includes the treatment of specific boundary conditions and the adaption of the force computation. First results are presented that showcase the damping properties of such particle-filled spheres in a bouncing experiment.

On Semeai Detection in Monte-Carlo Go - Graf, Tobias; Schaefers, Lars; Platzner, Marco (Proc. Conf. on Computers and Games (CG))

Multi-Algorithmen-Rendering: Darstellung heterogener 3-D-Szenen in Echtzeit - Petring, Ralf

Generating Modelica Models from Software Specifications for the Simulation of Cyber-physical Systems - Pohlmann, Uwe; Holtmann, Jörg; Meyer, Matthias; Gerking, Christopher (Proceedings of the 40th Euromicro Conference on Software Engineering and Advanced Applications (SEAA))

The MechatronicUML Method: Model-Driven Software Engineering of Self-Adaptive Mechatronic Systems - Becker, Steffen; Dziwok, Stefan; Gerking, Christopher; Heinzemann, Christian; Schäfer, Wilhelm; Meyer, Matthias; Pohlmann, Uwe (Proceedings of the 36th International Conference on Software Engineering (Posters))

A Modelica Coordination Pattern Library for Cyber-Physical Systems - Pohlmann, Uwe; Dziwok, Stefan; Meyer, Matthias; Tichy, Matthias; Thiele, Sebastian (Proceedings of the 7th International ICST Conference on Simulation Tools and Techniques)

The MechatronicUML Design Method - Process and Language for Platform-Independent Modeling - Becker, Steffen; Dziwok, Stefan; Gerking, Christopher; Schäfer, Wilhelm; Heinzemann, Christian; Thiele, Sebastian; Meyer, Matthias; Priesterjahn, Claudia; Pohlmann, Uwe; Tichy, Matthias

Viewpoints and Views in Hardware Platform Modeling for Safe Deployment - Pohlmann, Uwe; Meyer, Matthias; Dann, Andreas Peter; Brink, Christopher (Proceedings of the 2Nd Workshop on View-Based, Aspect-Oriented and Orthographic Software Modelling)

Ein selbst-stabilisierender Algorithmus für das Finite Sleep Problem in Skip+ Graphen - Luo, Linghui

Formbildung selbstorganisierender Partikelsysteme - Hinnenthal, Kristian

Incorporating feedback from application layer into routing and wavelength assignment algorithms - Wette, Philip; Karl, Holger (2013 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

SKIP*: A Self-Stabilizing Skip Graph - Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (J. ACM)

Brief announcement: amoebot - a new model for programmable matter - Derakhshandeh, Zahra; Dolev, Shlomi; Gmyr, Robert; W. Richa, Andrea; Scheideler, Christian; Strothmann, Thim Frederik (26th ACM Symposium on Parallelism in Algorithms and Architectures, SPAA'14, Prague, Czech Republic - June 23 - 25, 2014)

Feature models supporting trade-off decisions in early mechatronic systems design - Kühn, Arno; Bremer, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (NordDesign 2014, Espoo, Finnland, 27. - 29. Aug. 2014)

Der Spitzencluster it's OWL auf dem Weg zur Industrie 4.0 - Gausemeier, Jürgen; Dumitrescu, Roman; Jasperneite, Jürgen; Kühn, Arno; Trsek, Henning (ZWF - Zeitschrift für Wirtschaftlichen Fabrikbetrieb)

Terrain Classification for Track-driven Agricultural Robots - Mahadhir, Khairul Azmi; Tan, Shing Chiang; Low, Cheng; Dumitrescu, Roman; Amin, Adam Tan Mohd; Jaffar, Ahmed (Procedia Technology)

Specification Technique CONSENS for the Description of Self-optimizing Systems - Dorociak, Rafal; Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter (Design Methodology for Intelligent Technichal Systems)

Strategy controlling for innovation clusters - the example of "it's OWL" - Kühn, Arno; Kliewe, Daniel; Dumitrescu, Roman; Gausemeier, Jürgen (ISPIM Conference 2014)

Systematische Berücksichtigung von Fertigungsanforderungen im Model-Based Systems Engineering - Dumitrescu, Roman; Fechtelpeter, Christian; Kühn, Arno (Tag des Systems Engineering, Bremen)

Methodology for the identification of solution patterns within mechatronic systems - Rabe, Martin; Anacker, Harald; Dumitrescu, Roman (Proceedings of the 15th International Workshop on Research and Education in Mechatronics (REM), El Gouna, Egypt)

Collaboration in Model-Based Systems Engineering based on Application Scenarios - Tschirner, Christian; Kaiser, Lydia; Dumitrescu, Roman; Gausemeier, Jürgen (NordDesign 2014)

Optimized process sequences for prototyping of molded interconnect devices - Jürgenhake, Christoph; Fechtelpeter, Christian; Dumitrescu, Roman; Heidsiek, Daniel (Advanced Materials Research)

Method for the Identification and Comparison of Alternative Process Chains Focusing on Economics Efficiency Analysis during the Conceptual Design of Mechatronic Integrated Devices - Schierbaum, Thomas; Gausemeier, Jürgen; Dumitrescu, Roman (Advanced Materials Research)

A Summer Blender Camp: Modeling, Rendering, and Animation for High School Students - Bailey, M.; Law, C. (IEEE Computer Graphics and Applications)

Student Projects Involving Novel Interaction with Large Displays - Dias, P.; Sousa, T.; Parracho, J.; Cardoso, I.; Monteiro, A.; Santos, B. S. (IEEE Computer Graphics and Applications)

Beyond Minecraft: Facilitating Computational Thinking through Modeling and Programming in 3D - Repenning, A.; C. Webb, D.; Brand, C.; Gluck, F.; Grover, R.; Miller, S.; Nickerson, H.; Song, M. (IEEE Computer Graphics and Applications)

Incorporating Modern OpenGL into Computer Graphics Education - Reina, G.; Müller, T.; Ertl, T. (IEEE Computer Graphics and Applications)

Creative Educational Use of Virtual Reality: Working with Second Life - Cao, M.; Li, Y.; Pan, Z.; Csete, J.; Sun, S.; Li, J.; Liu, Y. (Computer Graphics and Applications, IEEE)

Graphical Qualities of Educational Technology: Using Drag-and-Drop and Text-Based Programs for Introductory Computer Science - DiSalvo, B. (IEEE Computer Graphics and Applications)

Variational Approach to Molecular Kinetics - Nüske, Feliks; Keller, Bettina G.; Pérez-Hernández, Guillermo; Mey, Antonia S. J. S.; Noé, Frank (Journal of Chemical Theory and Computation)

Towards a Simulation-based Approach for Evaluating Business Models for the Electric Vehicle Market

Linguistic Consistency of Goal Models - Pittke, Fabian; Nagel, Benjamin; Engels, Gregor; Mendling, Jan (Proceedings of the 19th International EMMSAD Conference)

Breathing Life into Situational Software Engineering Methods - Fazal-Baqaie, Masud; Gerth, Christian; Engels, Gregor (In Proceedings of the 15th International Conference of Product Focused Software Development and Process Improvement (PROFES 2014))
Software engineering methods are used to prescribe and coordinate the tasks necessary to plan, build, deliver, and maintain software. There is a broad consensus that there is no one-size-fits-all method and that, e.g., agile and plan-driven approaches have to be mixed sometimes, based on the context of a project. Creating these so-called situational methods and assuring that they cover all necessary details consistently is a challenge. There is also the challenge for the project teams to follow methods as prescribed by the method engineer. Our approach supports the creation of consistent situational methods from a repository of pre-existing building blocks. Moreover, we present means to enact these methods with standard BPEL/BPEL4People workflow engines, automating the coordination of tasks and providing guidance for them.

Agile Entwicklung mit On- und Offshore-Partnern – Methodenverbesserung in der Praxis - Fazal-Baqaie, Masud; Sauer, Stefan; Heuft, Torsten (Proceedings of Projektmanagement und Vorgehensmodelle 2014)
Agile Softwareentwicklungsmethoden erfreuen sich einer steigenden Verbreitung, versprechen sie doch risiko-getrie-ben und leichtgewichtig auch bei sich verändernden Anforderungen gute Ergebnisse zu erzielen. Viele Unternehmen stehen jedoch vor der Herausforderung, agile Prinzipien mit den Gegebenheiten im Unterneh-men zu vereinbaren, z.B. mit den internen Prozessen und organisatori-schen Gegebenheiten. Ein besonders herausforderndes Beispiel ist die Softwareentwicklung in Kooperation mit Offshore-Partnern. Die Auto-ren berichten aus einem laufenden Methodenverbesserungsprojekt für ein Unternehmen der Finanzbranche, das für die Softwareentwicklung mit On- und Offshore-Partnern kooperiert. Anders als bisher soll der indischen Offshore-Partner in naher Zukunft große Softwaressysteme federführend implementieren. Dabei sollen projektindividuell auch Onshore-Partner eingebunden werden. Der Beitrag stellt den systema-tischen Ansatz für die inkrementelle Methodenverbesserung vor, mit dem Varianten einer möglichst agilen Methode definiert werden sollen, die sowohl im Projektumfeld als auch im operativen Tagesgeschäft ef-fektiv und effizient eingesetzt werden können. Die Autoren fassen au-ßerdem die im Rahmen von Interviews erhobenen, bisherigen Erfah-rungen in der Zusammenarbeit mit dem Offshore-Partner zusammen, die für die Methode berücksichtigt werden müssen.

Configuration of Specification Language and Matching for Services in On-The-Fly Computing - Arifulina, Svetlana; Christin Platenius, Marie; Gerth, Christian; Becker, Steffen; Engels, Gregor; Schäfer, Wilhelm

Model-Based User Interface Development for Adaptive Self-Service Systems - Yigitbas, Enes; Fischer, Holger Gerhard; Sauer, Stefan (Design, User Experience, and Usability. Theories, Methods, and Tools for Designing the User Experience - Third International Conference, DUXU 2014, Held as Part of HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014, Proceedings, Part I)

Model-Based Development of Adaptive UIs for Multi-channel Self-service Systems - Yigitbas, Enes; Fischer, Holger Gerhard; Kern, Thomas; Paelke, Volker (Human-Centered Software Engineering - 5th IFIP WG 13.2 International Conference, HCSE 2014, Paderborn, Germany, September 16-18, 2014. Proceedings)